Intestinal IL-22RA1 signaling regulates Chlamydia deficient in plasmid-encoded pGP3 spreading to large intestine - Tian, Qi; Fang, Guangchi; Ma, Jingyue; Wang, Luying; Zuo, Zonghui; Zhang, Tianyuan (Frontiers in Microbiology, 2025)
Chlamydia trachomatis is the most important infectious cause of tubal infertility and is frequently detected in the human gastrointestinal tract. Chlamydia muridarum, a murine pathogen, closely resembles the human pathogen C. trachomatis. Our previous studies showed that the pGP3-deficient C. muridarum mutant was restricted to the large intestine following intracolonic inoculation, suggesting that the pGP3-deficient mutant was killed by the tissue beyond the large intestine. Here, we report that the intra-ilenum, but not the intra-jejunum, to bypass the gastric barrier rescued the colonization of pGP3-deficient C. muridarum, suggesting that pGP3 is required to overcome host factors of the jejunum to help C. muridarum reach the colon. Moreover, mice genetically deficient in IL-22 not only rescued the colonization of pGP3-deficient C. muridarum following intrajejunal inoculation but also rescued the colonization of pGP3-deficient C. muridarum in the whole gastrointestinal tract tissues following intracolonic inoculation on day 14, suggesting a critical role of IL-22 in regulating chlamydial spread. Importantly, IL-22RA1 flox/flox and Villin-cre mice rescued the colonization of pGP3-deficient C. muridarum following intrajejunal inoculation, suggesting that intestinal epithelial-specific IL-22RA1 signaling is important for the spread of pGP3-deficient C. muridarum from the small intestine to the large intestine. These observations provide a platform for further research on intestinal IL-22RA1 signaling in regulating bacterial spread in the intestine. Therefore, host factors identified in the gastrointestinal tract may also contribute to the female lower genital tract barrier during sexually transmitted diseases.